THE TAXATION OF ELECTRONIC COMMERCE AS SPONSOR OF BASIC INCOME: COMPENSATING SOCIAL INEQUALITIES IN THE CONTEXT OF BRAZILIAN AUSTERITY POLICY (Revista Inclusiones, 2021)
The situation of socioeconomic vulnerability in the context of the pandemic by COVID-19 resumedthe discourse on basic income. In a scenario of financial recession, Brazil does not seem to have theresources to pay for this assistance policy. With a bibliographic and quantitative research, the workseeks to analyze the proposal for the taxation of electronic commerce as a potential sponsor of basicincome, since it is presented as a measure capable of compensating for the social inequalitiesaggravated by the Austerity Policy. It was noted that, despite the legislative initiatives, the taxation ofelectronic commerce is not something simple, but it involves a wide range of services andtechnological products that do not contain a legal provision and fall in normative lagoons. The TaxReform seems right to unify taxation by using electronic commerce, but there is something to bedesired when it is restricted to federal taxes and because it does not present a hypothesis of clearimpact.